MONEY DEMAND ANALYSIS IN INDONESIA: THE SVAR APPROACH - Reza Ananda Putra; Mahrus Lutfi Adi Kurniawan (Riset Ekonomi Pembangunan, 2021)
This study aims to analyze the response of demand for money to shocks in macroeconomic variables such as income, inflation and interest rates in Indonesia. The study used time-series data from 2008: Q1 - 2019; Q4 with SVAR approach. Based on the result there was a positive response from money demand to income shocks but a negative response to inflation and interest rate shocks. Income variable is volatile and contributes the most to money demand compared to inflation and interest rates.